Cost of diseases in Brazil: breast cancer, enteritis, cardiac valve disease and bronchopneumonia - Arredondo Armando; Lockett Lejeune Y.; Icaza Esteban de (Universidade de São Paulo, 1995)
The results from the need to develop methodologies for performing cost analysis in developing countries, principally in the region of Latin America, were studied. It, furthermore, serves to generate knowledge from an economic evaluation in order to support decision-making related to the organization of health systems, particularly in the efficient use of resources which are allocated for the provision of medical services. Two chronic diseases (breast cancer and cardiac valve disease) and two infections (enteritis and bronchopneumonia) were selected for the study. The results recommend the use of a valid methodology for economic cost analysis of any disease to be studied and the use of this information in the decision-making process.